Porównania przyrodnicze w powieści Olgi Tokarczuk "Prowadź swój pług przez kości umarłych" = Nature comparisons in Olga Tokarczuk`s novel "Drive your Plow over the Bones of the Dead" - Judek, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this statement is to characterize the comparisons in Olga Tokarczuk`s novel "Drive your Plow over the Bones of the Dead". Narration in the work is wrote entirely from the main character perspective, in which we can notice not only her relationship with nature, but also her great respect for it.
Keywords: Tokarczuk, Olga (1962- ); "Prowadź swój pług przez kości umarłych"; porównania; ekokrytyka; świat przyrody; język artystyczny; "Drive your Plow over the Bones of the Dead"; comparisions; ecocritics; world of nature; artistic language